Preparation, Purification, Identification and Anti-lipid Oxidation of Kidney Bean Skin Polyphenols - Lilan SUN; Kun WANG; Youliang ZHANG; Ruokun WANG; Feng ZUO (Shipin gongye ke-ji)
In order to explore the preparation and purification process of polyphenols from purple flower kidney bean skins and their anti-lipid oxidation effect, this study investigated the effects of solvent concentration, extraction temperature, extraction time, solid-liquid ratio and number of extraction on extraction amount of polyphenols from purple flower kidney bean skins by single factor experiments. Purified the crude extraction with HPD600 macroporous resin, and analyzed the phenolic composition using liquid chromatography-mass spectrometer. Shelf life predication model of peanut oil was established with peroxide value as the indicator using the Arrhenius equation. The experimental results showed that the optimal extraction conditions for kidney bean skin polyphenols were: ethanol concentration of 60%, extraction temperature of 70 ℃, extraction time of 40 min, solid-to-liquid ratio of 1:60 (g:mL), and 4 times of extraction, under these conditions, the extraction amount of polyphenols was 0.18±0.49 g/g. HPD600 had the highest static adsorption capacity and desorption rate, making it suitable for purifying polyphenols from purple kidney bean skins. The optimal purification conditions were: loading flow rate of 1.0 mL/min, ethanol concentration of 60%, elution flow rate of 1.0 mL/min, and the maximum purity of polyphenols was 54.68%±1.97%. Kidney bean skins contained 19 types of monomer phenols, with the highest catechin content at 425.952±7.652 µg/g. Adding kidney bean skin polyphenols or antioxidants could effectively delay the increase in peroxide value of edible oil. Using a model, it was calculated that peanut oil mixed with polyphenols-vitamin C had a maximum shelf life of 193.4 d at 20 ℃, control group was 150.3 d, with a maximum relative error of 8.7% compared to measured values, accurately predicting the shelf life of the edible oil. In conclusion, kidney bean skin polyphenols had strong antioxidant properties and potential as a safe natural food antioxidant.